Associated Topics || Dr. Math Home || Search Dr. Math

Objects in a Pyramid

Date: 7/8/96 at 9:6:16
From: Anonymous
Subject: Objects in a pyramid

Dear Dr. Math,

A number of objects are stacked in a triangular pyramid (e.g., top
layer 1, next layer 3, next layer 6, etc.).  How many objects are in
the nth layer from the top?  What is the total number of objects in
the top n layers?  I need formulas to prove these.

Nancy Geldermann

Date: 7/8/96 at 16:56:5
From: Doctor Pete
Subject: Re: Objects in a pyramid

Consider a single layer (shown below is the 5th layer):

*
* *
* * *
* * * *
* * * * *

Clearly, the n(th) layer contains 1+2+...+n objects.  Let this value
be S[n]. Note:

S[n] =   1 +   2 +   3 + ... + n-2 + n-1 +   n
+ S[n] =   n + n-1 + n-2 + ... +   3 +   2 +   1
-------------------------------------------------
2S[n] = n+1 + n+1 + n+1 + ... + n+1 + n+1 + n+1
= n(n+1)

=> S[n] = n(n+1)/2 .

Now, say we want to know the number of objects in the top m layers.
We have to take the sum of all these S[n] from n=1 to m.  That is, we
must find S[1]+S[2]+...+S[m].  Call this T[m].  Writing this in sigma
notation,

m                    m
\---\  n(n+1)     1  \---\
T[m] =  >    -------- = ---  >    n^2 + n
/---/    2        2  /---/
n=1                  n=1

m               m             m
1  \---\        1  \---\      1  \---\       m(m+1)
= ---  >    n^2 + ---  >    n = ---  >    n^2 + ------
2  /---/        2  /---/      2  /---/         4
n=1             n=1           n=1

Now we must find what the sum 1^2 + 2^2 + 3^2 + ... + m^2 is.  I
claim that this is m(m+1)(2m+1)/6.  We'll prove this by induction.
For m=1, this is true, since 1(1+1)(2+1)/6 = 1 = 1^2.  Suppose this
is true for some value of m.  Then 1^2 + 2^2 + 3^2 + ... + m^2 +
(m+1)^2 = m(m+1)(2m+1)/6 + (m+1)^2 = (m+1)((m(2m+1)/6)+(m+1)) =
(m+1)(2m^2+m+6m+6)/6 = (m+1)(2m^2+7m+6)/6 = (m+1)(m+2)(2m+3)/6 =
(m+1)(m+1+1)(2(m+1)+1)/6, so our assertion is true for m+1.
Hence the sum of the first m squares is m(m+1)(2m+1)/6.  Therefore,

m(m+1)(2m+1)   m(m+1)   m(m+1)            m(m+1)(m+2)
T[m] =  ------------ + ------ = ------ (2m+1+3) = ----------- .
12          4        12                   6

-Doctor Pete,  The Math Forum
Check out our web site!  http://mathforum.org/dr.math/

Associated Topics:
High School Basic Algebra
High School Discrete Mathematics

Search the Dr. Math Library:

 Find items containing (put spaces between keywords):   Click only once for faster results: [ Choose "whole words" when searching for a word like age.] all keywords, in any order at least one, that exact phrase parts of words whole words

Submit your own question to Dr. Math
Math Forum Home || Math Library || Quick Reference || Math Forum Search